FULL DIALLEL CROSSES FOR ESTIMATION OF GENETIC PARAMETERS IN MAIZE - & et al., Sadalla (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted to estimate some genetic parameters by using full diallel crosses in maize (Zea mays L.) at Grdarasha Agricultural Research Station, College of Agriculture, University of Salahaddin, Erbil. During the spring season of 2015, four diverse maize inbred line seeds were sown and exhibited full diallel cross between them. In fall season 2015, the F1 hybrids with their parental lines were sown in randomized complete block design with three replications. The results revealed there were highly significant differences among genotypes for almost all of the evaluated traits which were days to 50% tasseling, plant height, ear height, ear length, no. of rows ear-1, 150-kernels weight and total yield except the character no. of ears plant-1. GCA and SCA mean squares were highly significant for some traits, but mean squares for reciprocal combining ability were highly significant for traits plant height, ear height and 150-kernels weight. Pertaining the parents, Kr 640 revealed the best values among the parents for most of the traits, and for diallel and reciprocal hybrids the crosses 3007× Kr 640 and 5012× Kr 640 demonstrated more desired values respectively. Regarding the σ2gca/σ2sca ratio, for all the traits exclude no. of rows ear-1, showed to be less than one, this showed the importance of non-additive gene effect in the inheritance of these traits, and the average degree of dominance were more than one in the same traits. Heritability estimation in both broad and narrow senses were proceed, the results submitted that heritability in broad sense was high for all the traits, it was recommended hybridization and selection method to improve these traits.